Meritokrasi dan Netralitas ASN dalam Pilkada: Analisis Normatif - Asia. A Parangrangi; A. Aswar; A. Hartawati; Zulviani Syam (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to analyze the neutrality of civil servants (ASN) within the framework of bureaucratic meritocracy in regional head elections (pilkada), with a particular focus on identifying structural and institutional factors that influence violations of neutrality. This research employs a normative legal method using statutory and conceptual approaches. Legal materials are classified into primary sources, including laws and regulations governing ASN neutrality, secondary sources such as books and scholarly articles, and tertiary sources including legal dictionaries. The analysis is conducted through qualitative and interpretative techniques to examine the consistency between legal norms and their implementation in practice. The findings reveal that the persistence of neutrality violations among civil servants is not primarily caused by the absence of legal regulation, but rather by weak implementation of the merit system, ineffective bureaucratic oversight, and inconsistent law enforcement. Supervision mechanisms tend to be reactive rather than preventive, while enforcement institutions face fragmentation of authority and lack of coordination. Furthermore, the legal culture within bureaucracy still tolerates political intervention, which undermines the principle of professionalism. In conclusion, the study demonstrates that ensuring ASN neutrality requires not only adequate regulatory frameworks but also institutional strengthening, integrated supervision systems, and consistent enforcement mechanisms. These findings contribute theoretically to the development of administrative law by emphasizing the importance of institutional capacity and legal culture and practically provide policy implications for improving bureaucratic governance and safeguarding democratic integrity in Indonesia.